PENGARUH PENGGUNAAN METODE QIRO’ATI DAN PERAN TEMAN SEBAYA TERHADAP KEMAMPUAN TAHSIN AL-QUR’AN SISWA - Anwar Hidayat; Naf’an Tarihoran (QATHRUNÂ, 2020)
This study aims to determine; 1) The influence of the use of the Qiro'ati method on the ability of students in the Qur'an, 2) The influence of the role of peers on the ability of students' Al Qur'an, 3) The influence of the use of the Qiro'ati method and the role of peers on the ability of Al-tahsin -Qur'an students on students of Madrasah Aliyah in Karangtanjung District Pandeglang Regency. This research is quantitative research. The population of this study consisted of 4 madrasas in Karangtanjung Subdistrict with a population of 465 students with a sample of 82 students using cluster sampling techniques. The research instrument was questionnaire and oral test. As for the results of the multiple regression test the influence of the use of the Qiro'ati method on the ability of students in Al-Qur'an obtained R square 0.760 means that it has a contribution of 76.0%, the influence of the role of peers on the ability of tahsin Al-Qur'an students obtained R square 0.662 means has a contribution of 66.2% and the influence of the use of the Qiro'ati method and the role of peers on the ability of the students of the Qur'an obtained R square 0.617 means that it has a contribution of 6.17%. The findings in this study 1) By using the Qiro'ati method the ability of the students to recite the Qur'an, 2) The role of peers helps the teacher in improving the ability of the students to recite the Qur'an, 3) Good by using the method of the Qiro'ati with the help of the peer role that exists in the Madrasah environment is very helpful in improving the ability of tahsin in students.